ANALISIS PENDAPATAN PETANI PESISIR PANTAI DI DESA WORI KECAMATAN WORI KABUPATEN MINAHASA UTARA (Income Analysis of Coastal Farmers in Wori Village of Wori District, North Minahasa Regency) - Lidya Marcelina Johanis; Ribka M. Kumaat; Lyndon Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research is to analyze and describe the income of coastal farmer in Wori Village, Wori Sub District, North Minahasa Regency. The study lasted for three months from July to September 2019 This study used primary data and secondary data. Primary data were obtained by direct interview using a questionnaire (questionnaire), while secondary data were obtained from the Wori Village Office, books available at local bookstores and the internet used the google search engine to access scientific journal articles and theses from other universities related with income of Coastal Farmers. The research results showed that the highest amount of income was from side jobs with an average of Rp. 1,312,000 / month and the lowest income was basic income with an average of Rp. 1,293.130 / month.Keywords: Income, Coastal Farmers